2010 Proceedings IEEE INFOCOM 2010
DOI: 10.1109/infcom.2010.5462077
|View full text |Cite
|
Sign up to set email alerts
|

P2P Trading in Social Networks: The Value of Staying Connected

Abstract: The success of future P2P applications ultimately depends on whether users will contribute their bandwidth, CPU and storage resources to a larger community. In this paper, we propose a new incentive paradigm, Networked Asynchronous Bilateral Trading (NABT), which can be applied to a broad range of P2P applications. In NABT, peers belong to an underlying social network, and each pair of friends keeps track of a credit balance between them. When user Alice provides a service (a file, storage space, computation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 19 publications
(26 reference statements)
0
28
0
Order By: Relevance
“…They have recently found applications in online rep utation systems [9] and P2P incentive paradigm design [10].…”
Section: Related Workmentioning
confidence: 99%
“…They have recently found applications in online rep utation systems [9] and P2P incentive paradigm design [10].…”
Section: Related Workmentioning
confidence: 99%
“…NABT [15] proposes the use of trust between friends to prevent freeriding behaviors using a more efficient form of tit-for-tat based on indirect trust relationships. NABT's credit-based approach can be viewed as a basic form of trust inference between friends of friends.…”
Section: Related Workmentioning
confidence: 99%
“…Research [3,[6][7][8] showed that such exchange paths do appear in P2P exchange due to its multilateral nature. Moreover, P2P reputation systems benefit from the use of structural ranking algorithms, such as EigenTrust [9] and Distributed PageRank [10], where connectivity properties of the network exchange influence the peer reputation.…”
Section: Introductionmentioning
confidence: 99%